Factors associated with loss to follow‐up after radiation therapy for head and neck cancer. Issue 4 (25th January 2022) - Hoyle, John M.; Correya, Tanya A.; Kenzik, Kelly; Francisco, Liton; Spencer, Sharon A.; Willey, Christopher D.; Bonner, James A.; Snider, James W.; Boggs, Drexell Hunter; Carroll, William R.; Bhatia, Smita; McDonald, Andrew M.
Abstract: Objectives: Head and neck cancer (HNC) patients are at high risk for late occurring radiation‐related morbidity and recurrence, necessitating close long‐term medical surveillance. This study identified factors associated with becoming lost to follow‐up (LTFU) at a comprehensive cancer center. Materials and Methods: Patients were drawn from survivors who received radiation for HNC at a single institution between 2001 and 2018. LTFU was defined as living patients without a clinical encounter within 2 years of the data query. Results: In total, 537 patients met the inclusion criteria and 57 (10.6%) were identified as LTFU. Individual comparisons identified time since completing radiation, non‐White race and being unmarried as associated with LTFU. Multiple regression identified time since treatment and being unmarried as factors associated with LTFU. A decision tree correctly sorted 89.4% using time, distance, and marital status. Conclusion: Time since radiation, distance to clinic, and being unmarried were factors associated with becoming LTFU.